Red cell distribution width predicts deaths in patients with acute pancreatitis - Wang, Dong (J Res Med Sci, 2015)
BACKGROUND: To investigate the association between the red cell distribution width (RDW) and mortality in patients with acute pancreatitis (AP), and to assess the ability of RDW to predict mortality in AP patients. MATERIALS AND METHODS: This retrospective cohort study included 120 patients (50 males and 70 females) with AP who were admitted to the First Affiliated Hospital of Zhongshan Medical University from January 2011 to October 2013. Demographic data and laboratory measures including RDW were obtained from medical records of each patient. A receiver operating characteristic (ROC) curve analysis was used to assess RDW values to predict the death of AP patients. RESULTS: The serum concentration levels of total Ca(2+) (P = 0.007) and albumin (P < 0.001), and the white blood cell counts (P = 0.005) were significantly lower, and the mortality rate (P < 0.001) and body mass index (P < 0.001) were significantly higher (P = <0.001, <0.001) in patients with RDW values of >13.4% than in patients with RDW values of ≤13.4%. RDW values were negatively correlated with the serum concentration levels of albumin (r = −0.212, P = 0.012) and total Ca(2+) (r = −0.206, P = 0.033), and were positively correlated with the patient's age (r = 0.201, P = 0.035). ROC analysis showed that the AUC for the RDW value was 0.894 (P < 0.001, 95% confidence interval = 0.823-0.966), and the optimal cut-off value to predict death was 14.35 (sensitivity = 88.2%, specificity = 91.8%). CONCLUSION: Red cell distribution width is a potentially new and sensitive predictor of mortality in patients with AP.